2013
DOI: 10.1186/1475-2840-12-22
|View full text |Cite
|
Sign up to set email alerts
|

Serum osteocalcin level and its association with carotid atherosclerosis in patients with type 2 diabetes

Abstract: ObjectiveTo investigate the association of serum osteocalcin with carotid atherosclerosis in patients with type 2 diabetes.MethodsWe performed a cross-sectional community-based study in metropolitan area. Serum total osteocalcin was measured by radioimmunoassay in 382 men and 435 postmenopausal women. The carotid artery intima-media thickness (IMT) and carotid plaques (PLQ) were measured by B-mode ultrasound.ResultsThe crude mean of serum osteocalcin concentrations were 4.52±2.43 ng/ml for men and 5.75±2.92 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…In addition, measurement of plasma OC concentration has also been proposed as a potential biomarker of cardiometabolic risk, along with its established clinical significance as a biomarker of bone turnover [5]. Reduced plasma OC levels were indeed found to be associated with greater incidence of pathological CV changes, like arterial and valvular calcification [6,7], carotid atherosclerosis [8], and increased carotid intima-media thickness [9]. Moreover, reduced circulating OC levels have consistently been associated with the presence of insulin resistance, metabolic syndrome and type 2 diabetes mellitus (T2DM) [10,11], clearly linked to atherosclerosis development [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, measurement of plasma OC concentration has also been proposed as a potential biomarker of cardiometabolic risk, along with its established clinical significance as a biomarker of bone turnover [5]. Reduced plasma OC levels were indeed found to be associated with greater incidence of pathological CV changes, like arterial and valvular calcification [6,7], carotid atherosclerosis [8], and increased carotid intima-media thickness [9]. Moreover, reduced circulating OC levels have consistently been associated with the presence of insulin resistance, metabolic syndrome and type 2 diabetes mellitus (T2DM) [10,11], clearly linked to atherosclerosis development [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition Sheng et al[15] observed that reduced osteocalcin is associated with increased risk of carotid atherosclerosis plaques in type 2 diabetes patients. They indicated decreased serum concentration of osteocalcin as a high risk for carotid atherosclerotic plaques and presented osteocalcin as a promising candidate for risk assessment of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, elevated OCN levels were accompanied by decreased BMD. This result might be attributed to retarded growth and deficient glucose metabolism [50,51]. Several researches declare that BMD and osteocalcin level can be influenced by estrogen, calcium and fat mass, resulting in decreased BMD and increased osteocalcin level [52,53].…”
Section: Discussionmentioning
confidence: 99%